Farm management and varietal choice in cassava-based production systems in Colombia - Rivera Vasco, Tatiana Carolina; Labarta, Ricardo Antonio; Andrade, Robert Santiago; Calle, Fernando; Becerra López Lavelle, Luis Augusto (2021)
Cassava is a commodity root crop grown globally for food and industrial purposes. In Colombia, it is the ninth most planted agricultural product involving more than 140 thousand farmers. Despite the key role it plays in the Colombian agricultural sector, information regarding the crop’s management or how cassava growers select on cultivars to grow for different purposes is limited or inexistent. This working paper exploits two separate primary data surveys at household-level in the Caribbean region and Cauca main cassava growing areas of Colombia. These data allowed to characterize these cassava production systems and discuss how to improve and strengthen this important agricultural sector. Detailed plot and household-level data was collected from 306 cassava growers in Cauca Department in 2014 and 395 cassava growers in Bolívar, Sucre, Córdoba, and Magdalena departments (known as the Caribbean region) in 2017. The analysis incorporates on-farm identification of cassava varieties using DNA fingerprinting analysis, providing insight into households’ decision about cassava variety management and the relative importance of these varieties in the country. The results indicate that most producers surveyed are smallholders, with agriculture as their principal occupation. These farmers have low or no access to extension services and low yields are observed when improved varieties have not been adopted vis-à-vis the national average, with large heterogeneity among departments. Regarding improved varieties, we identified low rates of adoption and considerably yields differences when compared with those farmers using non-improved germplasm. Thus, our results depict the importance of increasing the dissemination and adoption of improved varieties, which can help to close yield gaps and improve producers’ livelihoods. Furthermore, DNA analysis was a valuable tool to improve variety identification and helps to map the areas under improve against land races and accurate disaggregate the crop productivity. Finally, these households present high vulnerability according to poverty scorecards and ELCSA indicators, accompanied by low levels of education for all family members.